Exploring the optimized strategy in the nitritation-anammox biofilm process for treating low ammonium wastewater. (January 2021) - Zheng, Zhaoming; Li, Jun; Chen, Guanghui; Peng, Yongzhen
Highlights: Three typical operational strategies were evaluated in the SNAD biofilm reactor. The highest TIN removal rate in the SBR cycle reached 0.523 kg N/m 3 /d. PN was the dominant EPS content on the SNAD biofilm. Candidatus Anammoxoglobus maintained high abundance in different conditions. The preferable strategy was low DO (0.7 mg/L) and long aeration period (180 min). Abstract: The main challenge for achieving the simultaneous nitritation, anammox and denitrification (SNAD) process is to optimize the concentrations of nitrite and dissolved oxygen (DO). This study explored the performance of SNAD biofilm reactor under three operational strategies. At Stage 1, 2 and 3, the average concentrations of DO were 0.7, 2.7 and 5.2 mg/L, respectively. The peak concentrations of NO2 – -N in the sequencing batch reactor (SBR) cycle were 5.3, 6.0 and 2.7 mg/L, respectively. The average removal rates of total inorganic nitrogen (TIN) were 0.30, 0.42 and 0.22 kg N/m 3 /d, respectively. Protein (PN) was the dominant extracellular polymeric substance (EPS) content on the SNAD biofilm. The PN concentration remained stable while the polysaccharide (PS) concentration changed rapidly under different operational strategies. High-throughput sequencing analysis indicated that high DO and long aeration period condition could lead to a slight decrease in the abundances of denitrifying bacteria and anammox bacteria.